Digital Takhrij Hadith as Islamic Digital Humanities: Reconstructing Epistemic Authenticity and Transmission in the Digital Age - Adelia, Naurah; Wahid, Abd; Alif, Muhammad; Andaluzi, Fahmi (Digital Muslim Review, 2025)
This study examines Digital Takhrij Hadith through the lens of Islamic Digital Humanities (IDH), proposing an epistemic framework for verifying and preserving hadith authenticity in the digital era. Using a systematic literature review and interpretative digital analysis, it explores how digital infrastructures—such as metadata provenance, semantic modeling, and AI-assisted verification—extend the classical logic of isnād, matn, and amānah al-naql. The proposed Digital Takhrij Epistemic Model (DiTEM) unites epis-temological integrity, ontological coherence, and ethical accountability to ensure trust-worthy digital transmission of hadith. Findings show that digitization, when guided by Islamic epistemology, enhances access and scholarly collaboration without compromising authenticity. Rather than replacing traditional scholarship, digital takhrij revitalizes it, transforming digital platforms into ethically grounded ecosystems of ʿilm. This synthesis demonstrates that digital technology can serve not as disruption but as ihyāʾ al-ʿilm—the revival of sacred knowledge through responsible innovation.